Narwhal and Jelly: Narwhalicorn and Jelly - Book 7 7, Narwhalicorn and Jelly - Clanton, Ben, 1988- (Toronto : Tundra Books, 2022)
"Narwhal wishes to see a unicorn -- and actually becomes one! When Jelly wonders what a unicorn is, Narwhal explains that they're pretty much narwhals of the land (!) -- and then gets carried away with a grand plan to see one. With the help of Star, Narwhal's wish comes true in the wildest, weirdest way: Narwhal gets some land legs and takes their first step ashore. After some wibble-wobbling and a bit of practice, Narwhal is soon galloping along in search of unicorns, though Jelly is a little land sick. Before they know it, Star has the duo blasting off to a magical planet where everyone is a unicorn!"--
Unicorns: narwhals of the land --
Keywords: Narwhal -- Comic books, strips, etc; Unicorns -- Comic books, strips, etc; Jellyfishes -- Comic books, strips, etc; Friendship -- Comic books, strips, etc; Wishes -- Comic books, strips, etc; Marine animals -- Comic books, strips, etc; Narwhal -- Fiction; Unicorns -- Fiction; Jellyfishes -- Fiction; Friendship -- Fiction; Wishes -- Fiction; Marine animals -- Fiction; Humorous comics; Comics (Graphic novels); Graphic novels